2017
DOI: 10.1186/s41606-017-0011-x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships and CPAP adherence among women with obstructive sleep apnea

Abstract: Background: Obstructive sleep apnea contributes to daytime sleepiness, poor quality of life and increased risk for heart disease and hypertension among women. Continuous positive airway pressure improves sleepiness and quality of life and may reduce health risks but few studies have evaluated predictors of adherence among women. The goal of this study was to evaluate the role of relationship factors in women's continuous positive airway pressure (CPAP) adherence and change in relationship quality among married… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Adherence has been defined differently in different studies; limited data in women suggests it is lower but results have been contradictory. 45 In one study, women were 1.72 times more likely to be nonadherent to CPAP therapy compared to men, even after adjusting to race, marital status, and age; in another study women showed less hours of use. 46,47 Fourteen months of data from the sleep center in Helsinki University Hospital showed that women were 1.2 times more likely to switch masks than men even after initial individualized mask fitting and that patients who switched masks had 7 times higher risk for stopping CPAP therapy within 1 year.…”
Section: Treatment Differencesmentioning
confidence: 97%
See 2 more Smart Citations
“…Adherence has been defined differently in different studies; limited data in women suggests it is lower but results have been contradictory. 45 In one study, women were 1.72 times more likely to be nonadherent to CPAP therapy compared to men, even after adjusting to race, marital status, and age; in another study women showed less hours of use. 46,47 Fourteen months of data from the sleep center in Helsinki University Hospital showed that women were 1.2 times more likely to switch masks than men even after initial individualized mask fitting and that patients who switched masks had 7 times higher risk for stopping CPAP therapy within 1 year.…”
Section: Treatment Differencesmentioning
confidence: 97%
“…39 Other factors such as being married or living with a partner, greater perceived social support, and higher relationship quality (less conflict) have been predictive of higher adherence in women. 45 Treatment options have been traditionally developed and tested in men including interfaces and auto-titrating CPAP machine algorithms. New algorithms with longer ramps, aiming at being more responsive to flow limitation and better at treating REM events have been recently developed.…”
Section: Treatment Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some individuals struggle using their PAP machine, which they believe identifies them as ill, odd or not able to take care of themselves [50][51][52][53] or they experience side effects, which have repeatedly been voiced as a barrier to continued PAP use 50,51,[54][55][56][57] . Social support can help many patients increase their PAP use and includes spousal support 50,51,[54][55][56]58,59 . However, not all spousal input is the same and partners who are too invasive can negatively impact on PAP use 58 .…”
Section: Patients' Perspective: Qualitative Research In Pap Usagementioning
confidence: 99%
“…Social support can help many patients increase their PAP use and includes spousal support 50,51,[54][55][56]58,59 . However, not all spousal input is the same and partners who are too invasive can negatively impact on PAP use 58 . Regular PAP users find themselves having to utilise internal means, such as willpower, positive attitudes and self-efficacy 54,55,60 , and engage in a cost-benefit evaluation 55,59 .…”
Section: Patients' Perspective: Qualitative Research In Pap Usagementioning
confidence: 99%